2020
DOI: 10.3390/v12111238
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Prevalence of HIV-1 Transmitted Drug Resistance in Portugal: Implications for First Line Treatment Recommendations

Abstract: Introduction: Treatment for All recommendations have allowed access to antiretroviral (ARV) treatment for an increasing number of patients. This minimizes the transmission of infection but can potentiate the risk of transmitted (TDR) and acquired drug resistance (ADR). Objective: To study the trends of TDR and ADR in patients followed up in Portuguese hospitals between 2001 and 2017. Methods: In total, 11,911 patients of the Portuguese REGA database were included. TDR was defined as the presence of one or more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…Between 2017 and 2019, an increasing trend was observed for TDR and all drug classes. This increasing trend in TDR had already been observed by our study group in a longitudinal study that included patients between 2001 and 2017 ( Pingarilho et al, 2020 ), as well as in a study published by a Canadian group ( Rocheleau et al, 2018 ). This increase could be related to population mobility and an increase in the number of migrants from Portuguese-speaking Sub-Saharan African countries, where TDR has been increasing in the last few years ( Rhee et al, 2015 ; Pingarilho et al, 2018 ; Sebastião et al, 2019 ; Pimentel et al, 2020 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Between 2017 and 2019, an increasing trend was observed for TDR and all drug classes. This increasing trend in TDR had already been observed by our study group in a longitudinal study that included patients between 2001 and 2017 ( Pingarilho et al, 2020 ), as well as in a study published by a Canadian group ( Rocheleau et al, 2018 ). This increase could be related to population mobility and an increase in the number of migrants from Portuguese-speaking Sub-Saharan African countries, where TDR has been increasing in the last few years ( Rhee et al, 2015 ; Pingarilho et al, 2018 ; Sebastião et al, 2019 ; Pimentel et al, 2020 ).…”
Section: Discussionsupporting
confidence: 83%
“…For example, TDR levels are highly discrepant when we compare Germany (18.4%) ( van de Laar et al, 2019 )[9], Belgium (15.7%) ( van de Laar et al, 2019 )[9], Hungary (7.1%) ( van de Laar et al, 2019 )[9], Netherlands (12.3%) ( van de Laar et al, 2019 )[9], Mozambique (14.0% in women) ( Pina-Araujo et al, 2014 )[10], Latin America (7.7%) ( Avila-Rios et al, 2016 )[11], and Washington DC (20.0%) ( Aldous et al, 2017 )[12]. Portugal, on the other hand, presented an overall TDR of 9.4% between 2001 and 2017, with a significantly increasing trend from 7.9% in 2003 to 13.1% in 2017 ( Pingarilho et al, 2020 ). These results were obtained in a retrospective study of our study group and were based only on RegaDB, a laboratory database including clinical, demographic, and genomic data of patients followed up in hospitals located in the southern region of Portugal.…”
Section: Introductionmentioning
confidence: 99%
“…The TDR prevalence in the first time-period was closer to the one from a study conducted in Portugal between 2001 and 2017 and that same study indicated an increase trend for TDR. Our ADR prevalence for Portugal in the first time-period, had a lower value than the overall ADR prevalence from that study, although the decreasing trend was concordant ( Pingarilho et al, 2020 ).…”
Section: Discussionmentioning
confidence: 51%
“…Today, 73% of people living with HIV have access to ART. Drug resistance could be acquired drug resistance (ADR), due to selective pressure of antiretrovirals (ARVs) in individuals, or transmitted drug resistance (TDR) due to an infection by HIV strains that harbor drug resistance mutations (DRMs; Clutter et al, 2016 ; Pingarilho et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the most common mutations, M184V rates presented a decrease over the yrs (76.88% in 2008 to 51.48% in 2017). This decrease on acquired DRM was also observed in other countries and was hypothesized to be due to an improvement on treatment efficacy and also an increased accessibility to ART which enhances patient adherence to therapy [ 44 , 45 , 46 ]. Moreover, in Brazil, pretreatment genotyping has been extended to children living with HIV under 12 years of age, in case of Mtb co-infection, to pregnant woman and new diagnoses with a sexual partner on ART, since 2013 [ 47 ], which may had an impact the on the SDRM general decrease trend.…”
Section: Discussionmentioning
confidence: 52%